Plasma Orexin-A Levels in Patients With Schizophrenia: A Systematic Review and Meta-Analysis - Li, Shaoli; Zhang, Ruili; Hu, Shaohua; Lai, Jianbo (Frontiers in Psychiatry, 2022)
Background: Orexins are polypeptides regulating appetite, sleep-wake cycle, and cognition functions, which are commonly disrupted in patients with schizophrenia. Patients with schizophrenia show a decreased connectivity between the prefrontal cortex and midline-anterior thalamus, and orexin can directly activate the axon terminal of cells within the prefrontal cortex and selectively depolarize neurons in the midline intralaminar nuclei of the thalamus. To address the relationship between orexin and schizophrenia, this study performed a meta-analysis on the alteration of plasma orexin-A levels in patients with schizophrenia. Method: We searched eligible studies in PubMed, Embase, Cochrane, and China National Knowledge Infrastructure (CNKI) from 1998 to September 3, 2021. A total of 8 case-control studies were included in the meta-analyses, providing data on 597 patients with schizophrenia and 370 healthy controls. The Stata version 16.0 software was used to calculate the Hedges’s adjusted g with 95% confidence intervals (CI). Results: The plasma orexin-A levels were not altered in subjects with schizophrenia (n = 597) when compared to healthy controls (n = 370). Subgroup analyses of gender (male and female vs only male), country (China vs other countries), medication (medication vs non-medication), and the measurement of plasma orexin-A (Enzyme-linked immunosorbent assay vs radioimmunoassay) revealed heterogeneity ranging from 30.15% to 98.15%, but none showed a significant alteration of plasma orexin-A levels in patients with schizophrenia. Heterogeneity was lower in the other countries and radioimmunoassay subgroup, while other subgroups remained to be highly heterogeneous. No significant evidence of publication bias was found either in Begg’s test or the Egger's test. Conclusion: The present meta-analysis indicated that patients with schizophrenia did not show abnormal plasma levels of orexin-A.